Kartläggning av energianvändning för Arena Oskarshamn - Karlsson, Martin; Gustafsson, Hanna (My University, 2007)
Indoor sports facilities, e.g. with ice and baths, require a substantial amount of energy to be operated in the Swedish climate. To combine sport facilities with different energy requirements and combine heating, air condition and cooling in one common service center is therefore a major approach in several new sport complexes. This report describes Arena Oskarshamn, a sports complex which includes a public bath, an ice hockey arena, and a combined playing field designed to suit bandy and football. The technical system is built around a heat pump/cooling machine. A combined technical system delivers energy in terms of heating and cooling to the different parts of the arena and depending on season energy can be utilized in various ways, making it very flexible. The aim of the report is to describe the sports complex in general and to summarize the system’s use of heating and cooling energy. The Arena’s energy use id determined by the characteristics and the requirements of the sport activities preformed, this could be described as the internal loads. External loads such as outdoor temperature, humidity and wind speed also affect the use of energy. The survey of the energy use in Arena Oskarshamn indicates that the heat pump can supply a majority of the required heating energy in the bath, while district is used to raise the temperature of the hot water and cover peak loads. There is however a need to install more meters in order to get a better understanding of the system and be able to make recommendations to improvements.
Keywords: Byggnadsteknik; Building engineering